Inhomogeneous Monte Carlo simulation of the vapor-liquid equilibrium of benzene between 300 K and 530 K - J.Janeček; H.Krienke; G.Schmeer (Condensed Matter Physics, 2007)
The inhomogeneous Monte Carlo technique is used in studying the vapor-liquid interface of benzene in a broad range of temperatures using the TraPPE potential field. The obtained values of the VLE parameters are in good agreement with the experimental values as well as with the results from GEMC simulations. In contrast to the GEMC, within one simulation box the inhomogeneous MC technique also yields information on the structural properties of the interphase between the two phases. The values of the vaporization enthalpy and the vapor pressure very well satisfy the Clausius-Clapeyron equation.